PENGARUH AUDIT OPERASIONAL TERHADAP PENJUALAN TIKET BERLANGGANAN PADA PT. JASA MARGA - Puspitaningrum, Dwinita Ambar (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test and to analyze the influence of the implementation of operational audit to the toll subscribe ticket selling which has been carried out by PT Jasa Marga Surabaya Gempol branch, the data is the primary and secondary data, the object of the research is PT Jasa Marga Surabaya Gempol branch which is located on Plaza Tol Kota Satelit Jl. Mayjen Sungkono Surabaya. This research uses quantitative analysis case study method by formulating hypothesis which is done by using t-test and F-test and the following steps is conducting statistics test to accept or deny the hypothesis. The field research has been carried out as data collection technique. The field research is carried out by distributing questionnaires to the respondents. The result of analysis and discussion is that the presence of operational audit which has been carried out to this company has significant influence to the subscribe ticket selling although there is a minor mistake such as the lack of communication between the employees and the operational audit party. Improvement will always be conducted on the performance of operational audit so the influence of operational audit is in accordance with the procedure and the regulation in the company.Keywords: Auditing, Operational Audit, and Selling